Komunikasi Konflik Pada Pelaksanaan Dan Pasca Pilpres 2019 Di Media Sosial Twitter - Sitti Maesurah Sitti (KOMVERSAL, 2022)
Communication and interaction in social relations have the potential to create conflict, due to differences in opinion, knowledge, and so on. Like the conflict that occurred between supporters of the Jokowi-Amin and Prabowo-Sandi presidential candidates in the Indonesian presidential election 2019. The conflict occurred because of different interests, hopes and differences in choices between groups. The conflict is getting sharper when religious polarization is raised in it. The research was conducted through a qualitative approach with descriptive methods, using literature study data collection techniques. This study aims to describe conflict communication in the implementation and after the 2019 presidential election on social media is Twitter. The results showed that the delivery of hate speech is getting sharper in the 2019 presidential election. Swear words of hatred are reciprocated in order to satisfy the desire for support for the presidential candidate of his choice. Even the phenomenon of hate speech is increasing ahead of the 2024 presidential election, especially during the Covid 19 pandemic era, through the identity symbols with insult orientation, bad accusations, swearing and scolding, or considering the opposing party stupid, and giving bad labels.